Effect of Work Achievement Assessment, Experience and Position Promotion on Employee Performance PT. Conwood Indonesia - Enny Herdiyani; Hasrul Azwar Hasibuan; Rindi Andika (Rowter Journal, 2022)
This research was conducted to explain the partial or simultaneous influence of the variable performance appraisal, experience, promotion on employee performance at PT. Conwood Indonesia. The total population used is 70 respondents who work at PT. Conwood Indonesia was taken using a questionnaire which was used as a data collection method in this study. The results of the analysis show that there is a simultaneous significant effect between the three variables, and a partially significant influence between the variables of job performance appraisal and job promotion on performance, and the experience variable has no effect on employee performance at PT. Conwood Indonesia.